2016
DOI: 10.1038/ncomms10338
|View full text |Cite
|
Sign up to set email alerts
|

The Atg1–kinase complex tethers Atg9-vesicles to initiate autophagy

Abstract: Autophagosomes are double-membrane vesicles that sequester cytoplasmic material for lysosomal degradation. Their biogenesis is initiated by recruitment of Atg9-vesicles to the phagophore assembly site. This process depends on the regulated activation of the Atg1–kinase complex. However, the underlying molecular mechanism remains unclear. Here we reconstitute this early step in autophagy from purified components in vitro. We find that on assembly from its cytoplasmic subcomplexes, the Atg1–kinase complex become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
146
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(157 citation statements)
references
References 50 publications
(99 reference statements)
9
146
0
2
Order By: Relevance
“…In contrast to Atg13, Atg17 does not bind lipid membranes. 6,7 In agreement with an earlier study, 8 Atg17 interacts with Atg9. Specifically, the central crescent (a4 helix) of Atg17 binds to the cytoplasmic domain (residues 424-507 in S. cerevisiae) and a short N-terminal region (residues 281-316 in S. cerevisiae) of Atg9.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…In contrast to Atg13, Atg17 does not bind lipid membranes. 6,7 In agreement with an earlier study, 8 Atg17 interacts with Atg9. Specifically, the central crescent (a4 helix) of Atg17 binds to the cytoplasmic domain (residues 424-507 in S. cerevisiae) and a short N-terminal region (residues 281-316 in S. cerevisiae) of Atg9.…”
supporting
confidence: 92%
“…Combining the results of Rao et al 6 and Yamamoto et al 11 in reverse chronological order along with the previous research yields a model of Atg13 function within the Atg1 complex for tethering an Atg9 vesicle (Fig. 1).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Indeed, the autophagy process is executed by more than 30 Atg factors and associated proteins in response to stimuli. It is known that autophagy is initiated at the phagophore assembly site (PAS) in yeast [33]. Yamamoto et al demonstrated that the Atg13-mediated supramolecular assembly is responsible for autophagy initiation [34].…”
Section: Autophagy: a Brief Introductionmentioning
confidence: 99%